Pollutant Loading Analysis of Suspended Solid, Nitrogen and Phosphorus at Bertam Catchment, Cameron Highlands using MUSIC - Noh, N.S.M.; Sidek, L.M.; Haron, S.H.; Puad, A. H. M.; Selamat, Z. (International Journal of Engineering and Technology, 2018)
This paper aimed to analyze the pollutant loading composition of suspended solids, nitrogen and phosphorus in urban stormwater at Cameron Highlands which known as popular tourism, agriculture and function as reservoir water to generate electricity. Researchers found the urban stormwater quantity modeling has achieved sufficient accuracy benchmark. However, modeling stormwater runoff quality is relatively difficult and largely depends on catchment characteristics/land-uses. Model of Urban Stormwater Improvement Conceptualization (MUSIC) estimates pollutant transport from catchments and stormwater treatment through different application of Best Management Practices (BMPs). Result obtained from the observed and calculated data was compared with MUSIC's estimations under a similar scenario where no applications of BMPs. As a second scenario, series of treatment train is propose for each sub-catchments based on the suitability and verification on site that consists of constructed stormwater treatment BMPs (wetlands, bio-retention, on-site detention, sediment basin and gross pollutant traps). Implementation of BMPs reduce nearly 100% of gross pollutant, 65% - 83% TSS, 40% - 66% TP and 52% - 78% due to effectiveness of BMPs in treating the pollutant within different landuse. As a summary, MUSIC can conceptually determine the effectiveness of BMPs without giving a detailed design.